A Comparison of the Satisfaction Levels of Collegiate Student-Athletes and Their Non-Athlete peers with Their Collegiate Experience - Berty, Diane; Griffy, Loretta; Luckey, Joseph; Wiemers, Roger (My University, 2002)
Research examining the satisfaction level of student athletes with their overall collegiate experience has been minimal. This study examined the existence of differences between collegiate student-athletes' satisfaction and the satisfaction of their non-athlete peers. Participants were enrolled at a mid-sized, urban, state-supported university located in the southeastern United States. There was a total of 644 students participating in this study. Student-athletes represented 168 of the participants and the remaining 476 were students who were not members of an intercollegiate athletic team. Eleven scales of satisfaction were examined using the Noel-Levitz Student Satisfaction lnventory. The statistical analysis of the data indicated five scales to be significantly different. lncreased levels of satisfaction among the student-athletes were found on the scales of academic advisement, recrnitment and financial aid, and safety and security. Decreased levels of satisfaction were found on the scales of campus life and campus climate.
Keywords: satisfaction; college experience; non-athlete students